2016
DOI: 10.1002/pmic.201500265
|View full text |Cite
|
Sign up to set email alerts
|

Integration of transcriptomic and proteomic analysis towards understanding the systems biology of root hairs

Abstract: Plants and other multicellular organisms consist of many types of specialized cells. Systems-wide exploration of large-scale information from singe cell level is essential to understand how cell works. Root hairs, tubular-shaped outgrowths from root epidermal cells, play important roles in the acquisition of nutrients and water, in the interaction with microbe, and in plant anchorage, and represent an ideal model to study the biology of a single cell type. Single cell sampling combined with omics approaches ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 100 publications
1
7
0
Order By: Relevance
“…Genes involved in cell differentiation and root hair initiation might not be expressed in elongating root hairs such as those collected in this study (Wang et al , 2016). In contrast, in Arabidopsis, root hair cells including early trichoblasts were collected for downstream analyses (Lan et al , 2013).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Genes involved in cell differentiation and root hair initiation might not be expressed in elongating root hairs such as those collected in this study (Wang et al , 2016). In contrast, in Arabidopsis, root hair cells including early trichoblasts were collected for downstream analyses (Lan et al , 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Transcriptome and proteome studies are useful tools for advancing understanding of root hair function (Hossain et al , 2015; Wang et al , 2016). In Arabidopsis, a transcriptomic study identified a set of 208 ‘core’ root epidermal genes (Bruex et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The multiple and essential functions of the root hair clearly establish this cell type as a system biology model to investigate plant cell development, uptake of water and nutrients, and response to abiotic and biotic signals. Indeed, a number of genome-wide studies have been published using root hairs from several model and crop plants (Hossain et al, 2015 ; Wang et al, 2016 ). The present paper is conceived as a contribution to improved understanding of the molecular mechanisms underpinning the roles of root hairs in legumes.…”
Section: Introductionmentioning
confidence: 99%
“…This protein was involved in the metabolic pathways to regulate plants under drought stress (Rao et al, 2017). GTP binding proteins are up-regulated under drought stress and are involved in the root hair formation (Wang et al, 2016). In tef root, these genes were up-regulated and the morphology of tef roots under drought stress had less root hair development (Figure 1, Figure 6).…”
Section: Discussionmentioning
confidence: 99%